(untitled) (International Seven Journal of Multidisciplinary, 2026)
The demand for sustainable and biofunctional materials has driven the development of green hydrogels based on biopolymers and Amazonian bioactives. This study explores the incorporation of four Amazonian oils — Copaiba (Copaifera spp.), Murumuru (Astrocaryum murumuru), Brazil nut (Bertholletia excelsa), and Buriti (Mauritia flexuosa) — into alginate-based hydrogels for biomedical applications. Films were prepared using sodium alginate (2 %), glycerin (2 %), and sodium dodecyl sulfate (0.1 %), with calcium chloride (CaCl₂) crosslinking to enhance mechanical resistance and stability. Oils were added as emulsified phases. Resulting films were analyzed for visual appearance, thickness, solubility, and swelling. All oil-based films were homogeneous, transparent, and flexible. The control film showed 0.286 mm thickness, 45.71 % solubility, and 1601.13 % swelling. Murumuru oil produced the thinnest film (0.153 mm), increased solubility (62.72 %), and maintained high swelling (1531.10 %). Brazil nut oil yielded the thickest film (0.311 mm), with 54.05 % solubility and reduced swelling (901.10 %). Copaiba oil showed the lowest swelling (644.45 %), moderate thickness (0.230 mm), and solubility (57.86 %). Buriti oil had the lowest solubility (41.42 %), moderate thickness (0.230 mm), and swelling of 1204.53 %. Each oil induced distinct effects on film properties. Copaiba and buriti oils reduced swelling and solubility, suggesting suitability for moist environments like wound sites. Murumuru oil enhanced plasticity, favoring applications needing thinner, softer films. The results highlight the potential of Amazonian oils as natural functional agents for tailoring hydrogel properties and advancing sustainable, high-value biomedical materials.